The Level REER model in the External Balance Assessment (EBA) Methodology - Mano, Rui (IMF Working Papers; Working Paper, 2019)
This paper offers an empirical model of the drivers of the level of the Real Effective Exchange Rate (REER) that is now part of the IMF's methodology for the assessment of external positions, including exchange rates. It constructs a measure of the level of the REER and it offers a panel regression that considers a large number of cross-sectional and time varying factors, guided by the extensive literature. Its main contribution is to enhance our understanding of the cross-sectional determinants of the level of the REER, while taking into account the time-series drivers. The framework accounts for the much larger cross-sectional variation of the level REER, and can better explain the time series variation of level REER when these are based on GDP-deflators rather than on consumer price indices. The latter suggest there may be merits to broadening the assessments to include such measures, although further analysis is required.